Risky business: food fraud vulnerability assessments - Huisman, Wim (Crime, law and social change, 2022)
Major food fraud scandals of the last decade have created awareness of the need to strengthen companies’ ability to combat fraud within their own organizations and across their supply chains. The scandals compelled food companies and the food industry as a whole to take action and to protect companies and industries against the threat of food fraud. Stakeholders expect food companies to act proactively to mitigate food fraud risks. Certification schemes expect food producers to consider food fraud and to undertake food fraud vulnerability assessments and prepare control plans to mitigate fraud risks. This paper examines how vulnerability for food fraud on company level and supply chain level can be assessed using criminological theory. First, the paper discusses how such theory can be applied for assessing motivations and opportunities for internal and external actors to commit food fraud and assessing existing control measures to mitigate these vulnerabilities. Second, the paper discusses the SSAFE-tool in which these elements have been used in a survey for assessing food fraud vulnerability of companies in food supply chains. Third, the paper evaluates the results of the application of the SSAFE-tool to several food supply chain and tiers, including milk, spices, extra olive oil, organic foods and the food service industry.